PERTUMBUHAN EKONOMI SEBAGAI VARIABEL PEMODERASI PENDAPATAN ASLI DAERAH DAN BANTUAN PROPINSI TERHADAP BELANJA MODAL - Jaeni Jaeni; Greg. Anggana L (Faculty of Economic and Business Universitas STIKUBANK, 2016)
Regional autonomy makes the region able to develop in accordance with its capabilities and does not depend on the Central Government. Efforts to increase the Original Revenue will not give meaning if not followed by an increase in regional economic growth. This study aims to analyze the effect of Local Revenue and Provincial Assistance on Capital Expenditures Moderated by Regional Economic Growth The research was conducted in the administrative area of Central Java Province Regency, which is 35 districts / cities consisting of 29 districts and 6 municipalities. The analytical technique used moderate quasi-model regression with the basis of interaction. The results of the hypothesis show that the Original Revenue, Provincial Assistance, and Economic Growth affect the Capital Expenditure. While Economic Growth is also proven to moderate the influence of Original Revenue on Capital Expenditure. The results of this study show that the model is able to explain the variance of Capital Expenditure of 85.5%. Keywords: Local Revenue, Provincial Assistance, Economic Growth, Capital Expenditure.